A haplotype‐specific linkage disequilibrium pattern of monoamine oxidase A gene associated with regular smoking in women - Chiang, Shang‐Lun; Nithiyanantham, Srinivasan; Velmurugan, Bharath Kumar; Tu, Hung‐Pin; Lee, Chien‐Hung; Ko, Ying‐Chin (The journal of gene medicine, 2019)
Background Cigarette smoking in women is raising a public health problem. The X‐linked monoamine oxidase A (MAOA) was considered as a susceptibility gene to substance abuse of tobacco, but the evolutionary effect of MAOA may lead to a positive or negative association between genetic variations and smoking development among study regions. Methods Based on linkage disequilibrium (LD), we performed a haplotype‐based association to explore the effect of MAOA gene on women's smoking risk in a case‐control study. Results Genotyped single nucleotide polymorphisms (SNPs) of MAOA gene, rs5953210G>A, rs2283725A>G and rs1137070T>C, were significantly associated with current smoking risk in women, and the increased level of plasma MAO‐A activity was raised with per copy increment of risk allele in current smokers (P < .01). The haplotype patterns with minor haplotype frequency >.05 were constructed using the Expectation‐Maximization algorithm, and the haplotype‐specific A‐G‐C pattern raised the 2‐fold risk to develop regular smoking (P = .0005). In the diplotype analysis based on X‐inactivation mechanism relative to no and full dosage compensation, we showed that A‐G‐C haplotype not only increased regular smoking risk in a dose‐dependent manner (Ptrend = .0011) but also contributed to smoking risk in the dosage compensation mechanism. Compared to non‐smokers, the effect of A‐G‐C haplotype on random X‐activation was associated with the raised MAO‐A activity in women smokers (P < .05) although the lifetime cigarette consumption showed a difference that was not statistically significant. Conclusion This study provides information on MAOA LD‐based haplotype and diplotype patterns in women smoking.